Left Ventricular Rotational Abnormalities in Treated Hypopituitarism: Insights From the Three-Dimensional Speckle-Tracking Echocardiographic MAGYAR-Path Study - Kormányos, Árpád; Gyenes, Nándor; Horváth, Ágnes; Ambrus, Nóra; Lengyel, Csaba; Valkusz, Zsuzsanna; Nemes, Attila (Frontiers in Cardiovascular Medicine, 2021)
Introduction. Hypopituitarism is a rare, often underdiagnosed, complex hormonal disease caused by the decreased secretion of one or more hormones in the pituitary gland. The present study was designed to assess left ventricular (LV) rotational mechanics in patients with treated hypopituitarism. It was also aimed to find possible differences in these parameters according to the origin of hypopituitarism (congenital vs. acquired). Methods. The present prospective study involved 35 treated patients with hypopituitarism, however, 4 patients had to be excluded due to inferior image quality. The mean age of the remaining 31 cases was 56.3 ± 13.2 years (18 males). The control group consisted of 29 age- and sex-matched healthy volunteers (mean age: 55.3 ± 4.8 years, 14 males). In all cases a complete two-dimensional echocardiography examination was performed followed by three-dimensional speckle tracking echocardiography. Results. No significant differences could be found in LV volumes between the controls and patients with hypopituitarism and hypopituitary subgroups. LV apical rotation (8.1  5.1 degrees vs. 10.6  3.4 degrees, p0.05) and LV twist (11.9  5.3 vs. 15.1  3.8, p0.05) were impaired in the hypopituitary group with normally directed LV rotational mechanics as compared to the healthy controls. However, 13% of patients showed near absence of LV twist called as LV ‘rigid body rotation’ (LV-RBR). There were no significant differences regarding LV apical and basal rotations and twist between acquired and congenital hypopituitary subgroups. Conclusions. Impaired LV apical rotation and twist could be demonstrated in hypopituitarism regardless of its origin. In the present study with small number of patients with hypopituitarism LV-RBR was present in 13% of cases.